Male genital self-mutilation - Mago, Vishal (Medknow Publications, 2011)
Psychiatric case reports of male genital self-mutilation (GSM) in the literature are rare and mostly anecdotal. Most of them are connected with personality disorders (Goldfield and Glick, 1970; Wise et al., 1989). In men, psychosis is an important cause for GSM, causing up to 80% of automutilations.